Peningkatan Mutu Sirup Pala DP Segar Sari dengan Penambahan Kitosan Sebagai Pengawet Alami dan Penjernih - Shafira Nurfadhila; Sugeng Heri Suseno (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Nutmeg syrup is one of the processed nutmeg meat products that has high selling potential. One of the nutmeg syrup producers in the Bogor area is DP Segar Sari. The purpose of this activity is to find out the potential and problems related to the production of Segar Sari DP nutmeg syrup in Bubulak Sub-District, Dramaga Sub-District, Bogor Regency, West Java Province through the Six-Univeristies Iniatitive Japan-Indonesia Service and Learning Program (SUIJI-SLP) 2019. Method used in this activity are field studies and interviews with DP Segar Sari owners to find out the existing problems. The problem solving method is carried out by means of literature study. DP Segar Sari nutmeg syrup requires the addition of natural preservatives and purifiers to improve its quality. Based on literature studies, it is known that chitosan added to nutmeg syrup can influence the nature and characteristics of nutmeg syrup, with the right addition can optimize the selling value of nutmeg syrup. Chitosan is able to prevent the growth of bacteria and mold, thereby extending shelf life. Chitosan is also able to clear up nutmeg syrup so it looks more attractive. Keywords: Chitosan, sale value, preservatives, purifier, nutmeg syrup